PERANCANGAN WEBSITE INFORMASI KAIN ULOS BATAK TOBA SEBAGAI UPAYA PELESTARIAN - Dika Novianti; Nugroho Agus Haryano; Restyandito (Jurnal Terapan Teknologi Informasi, 2022)
User Interface (Interface) is a visual display that can bridge the system or application with the user. Therefore, the interface is an important thing for a system or application as it looks seen by the user. This interface is implemented on websites that are built easily for users. The website that was built aims to build user understanding that cultural preservation is important. The preservation of this culture is the Toba Batak Ulos Fabric from Medan, North Sumatra. Ulos cloth is a characteristic of the Batak tribe and has been continuously developed for generations. Therefore, the author built an interface website to help digitally preserve Ulos Fabrics that can be accessed by everyone. In this study, the website was built using the Goal- Directed Design method which consisted of 6 stages, namely Research, Modeling, Requirements, Framework Definition, Refinement, and Development Support. After completing the 6 stages, the website that was built was tested using the Usability Testing and System Usability Scale (SUS) methods. Usability Testing uses 2 aspects, namely Task Success and Time On Task, while the System Usability Scale uses questionnaires to 50 respondents. The final result of the test experienced a significant increase that the usability of the website was aboveaverage.